Public trials Burke, Zola, Arendt, and the politics of lost causes - Maxwell, Lida (Oxford Univ. Press, 2014)
"There are certain moments, such as the American founding or the Civil Rights Movement, that we revisit again and again as instances of democratic triumph, and there are other moments that haunt us as instances of democratic failure. How should we view moments of democratic failure, when both the law and citizens forsake justice? Do such moments reveal a wholesale failure of democracy or a more contested failing, pointing to what could have been, and still might be? Public Trials reveals the considerable stakes of how we understand democratic failure. Maxwell argues against a tendency in the thinking of Plato, Rousseau and contemporary theorists to view moments of democratic failure as indicative of the failure of democracy, insomuch as such thinking leads to a deference to authority that unintentionally encourages complicity in elite and legal failures to assure justice.
Includes bibliographical references and index
Keywords: Hastings, Warren, -- 1732-1818 -- Trials, litigation, etc; Burke, Edmund, -- 1729-1797; Dreyfus, Alfred, -- 1859-1935 -- Trials, litigation, etc; Zola, Emile, -- 1840-1902; Eichmann, Adolf, -- 1906-1962 -- Trials, litigation, etc; Arendt, Hannah, -- 1906-1975; POLITICAL SCIENCE / History & Theory; LAW / Public; PHILOSOPHY / Political; Philosophie; Democracy -- Philosophy; Justice, Administration of -- Philosophy; Politische Philosophie; Prozess; Demokratie